Effect of genetic polymorphisms rs2301113 and rs2057482 in the expression of HIF-1α protein in periodontal ligament fibroblasts subjected to compressive force - Erika Calvano KÜCHLER; Vinicius Broska TEODORO; Agnes SCHRÖDER; Ute NAZET; Michelle Nascimento MEGER; Patricia Valéria Manozzo KUNZ; Flares BARATTO-FILHO; Gerrit SPANIER; Rafaela SCARIOT; Peter PROFF; Christian KIRSCHNECK (University of São Paulo, 2023)
Abstract Objective Many genes and signaling molecules are involved in orthodontic tooth movement, with mechanically and hypoxically stabilized HIF-1α having been shown to play a decisive role in periodontal ligament signaling during orthodontic tooth movement. Thus, this in vitro study aimed to investigate if genetic polymorphisms in HIF1A (Hypoxia-inducible factor α-subunits) influence the expression pattern of HIF-1α protein during simulated orthodontic compressive pressure. Methodology Samples from human periodontal ligament fibroblasts were used and their DNA was genotyped using real time Polymerase chain reaction for the genetic polymorphisms rs2301113 and rs2057482 in HIF1A . For cell culture and protein expression experiments, six human periodontal ligament fibroblast cell lines were selected based on the patients' genotype. To simulate orthodontic compressive pressure in fibroblasts, a 2 g/cm2 force was applied under cell culture conditions for 48 hours. Protein expression was evaluated by Western Blot. Paired t-tests were used to compare HIF-1α expression with and without compressive pressure application and unpaired t-tests were used to compare expression between the genotypes in rs2057482 and rs2301113 (p<0.05). Results The expression of HIF-1α protein was significantly enhanced by compressive pressure application regardless of the genotype (p<0.0001). The genotypes in the genetic polymorphisms rs2301113 and rs2057482 were not associated with HIF-1α protein expression (p>0.05). Conclusions Our study confirms that compressive pressure application enhances HIF-1α protein expression. We could not prove that the genetic polymorphisms in HIF1A affect HIF-1α protein expression by periodontal ligament fibroblasts during simulated orthodontic compressive force.